DEEP LEARNING APPROACH BASED ON THE GASING METHOD TO ENHANCE ELEMENTARY STUDENTS’ MOTIVATION IN LEARNING MATHEMATICS - Carolin, Fransiska Evin (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This study aims to improve students' motivation to learn mathematics through the application of the GASING method in grade VI of SD Negeri 28 Gasing, Landak Regency. The background of this research is the low level of students’ motivation in learning mathematics, which is reflected in their limited active participation, low interest in following lessons, and lack of confidence in solving mathematical problems. This research employed classroom action research with a qualitative approach involving 24 students as the research subjects. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The results showed a significant improvement in students’ motivation to learn mathematics after the implementation of the GASING method. Students’ intrinsic motivation increased from 29.5% at the baseline to 54.16% in Cycle I and further improved to 66.66% in Cycle II. Meanwhile, students’ extrinsic motivation increased from 33.33% at the baseline to 52.08% in Cycle I and reached 70.83% in Cycle II. In conclusion, the implementation of the GASING method is effective in improving students’ motivation to learn mathematics.